UltraScience Net: High-Performance Network Research Test-Bed. (2009) - Rao Rao, Nageswara S. V. Nageswara S. V.; Wing Wing, William R. William R.; Hicks Hicks, Susan E. Susan E.; Poole Poole, Stephen W. Stephen W.; Denap Denap, Frank A. Frank A.; Carter Carter, Steven M. Steven M.; Wu Wu, Qishi Qishi
Abstract : The high-performance networking requirements for next generation large-scale applications belong to two broad classes: a) high bandwidths, typically multiples of 10Gbps, to support bulk data transfers, and b) stable bandwidths, typically at much lower bandwidths, to support computational steering, remote visualization, and remote control of instrumentation. Current Internet technologies, however, are severely limited in meeting these demands because such bulk bandwidths are available only in the backbone, and stable control channels are hard to realize over shared connections. The UltraScience Net (USN) facilitates the development of such technologies by providing dynamic, cross-country dedicated 10Gbps channels for large data transfers, and 150 Mbps channels for interactive and control operations. Contributions of the USN project are two-fold: a.   Infrastructure Technologies for Network Experimental Facility : USN developed and/or demonstrated a number of infrastructure technologies needed for a national-scale network experimental facility. Compared to Internet, USN's data-plane is different in that it can be partitioned into isolated layer-1 or layer-2 connections, and its control-plane is different in the ability of users and applications to setup and tear down channels as needed. Its design required several new components including a Virtual Private Network infrastructure, a bandwidth and channel scheduler, and a dynamic signaling daemon. The control-plane employs a centralized scheduler to compute the channel allocations and a signaling daemon to generate configuration signals to switches. In a nutshell, USN demonstrated the ability to build and operate a stable national-scale switched network. b.   Structured Network Research Experiments : A number of network research experiments have been conducted on USN that cannot be easily supported over existing network facilities, including test-beds and production networks. It settled an open matter by demonstrating that the performance of switched connections and Multiple Protocol Label Switching tunnels over routed networks are comparable. Furthermore, such connections can be easily peered, and the performance of the resultant hybrid connections is still comparable to the constituent pure connections. USN experiments demonstrated that Infiniband transport can be effectively extended to wide-area connections of thousands of miles, which opens up new opportunities for efficient bulk data transport. USN provided dedicated connections to Cray X1 supercomputer and helped diagnose TCP performance problems which might have been otherwise incorrectly attributed to traffic on shared connections. USN contributed to the development of transport methods for dedicated connections to other traffic. Recently, experiments were conducted to assess the performance of application acceleration devices that employ flow optimization and data compression methods to improve TCP performance.